Police Strategy in Tackling Liquor Abuse: An Analysis of Pre-emptive, Preventive and Repressive Based Strategies - Diannita Laya, Putri Nadhia (Judge : Jurnal Hukum, 2024)
This study aims to analyze the police strategy in tackling liquor abuse in East Bolaang Mongondow Regency with a pre-emptive, preventive, and repressive approach. The method used is qualitative with a case study approach. The results of the study show that pre-emptive efforts carried out through education and counseling through social media aim to increase public awareness about the dangers of alcohol, but are hit by low public awareness and a strong culture of alcohol consumption. Preventive efforts that include patrols and cooperation with related parties also experience obstacles, such as minimal supervision and the influence of the social environment that encourages alcohol consumption behavior. Meanwhile, repressive efforts in the form of cracking down on the circulation of illegal liquor and law enforcement, although necessary, have not been effective enough to reduce the rate of alcohol abuse. This study suggests that law enforcement should be firmer and a more comprehensive approach in educating and changing public behavior related to alcohol.